2022
DOI: 10.3389/fmed.2022.951793
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and related social distancing measures induce significant metabolic complications without prominent weight gain in Korean adults

Abstract: BackgroundThis study using multi-center health examination data from Korean adults was conducted to confirm changes in weight, and their related cardiometabolic parameters, before and after strengthening of social distancing regulations.MethodsA retrospective cohort study was conducted using health check-up data from 13 university hospitals. The study period was from January 2018 to July 2020. To examine the effect of systematic social distancing measures, participants who underwent a health check-up (Visit 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
4
2
0
Order By: Relevance
“…We used a retrospective longitudinal design with a broad follow-up period and paired data. Notably, our results are consistent with those of 2 previous longitudinal studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We used a retrospective longitudinal design with a broad follow-up period and paired data. Notably, our results are consistent with those of 2 previous longitudinal studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we maximized the inclusion period from the implementation of high-level social distancing to its abolishment. Furthermore, we obtained consistent results for both subgroups in the present study and confirmed the results of previous retrospective cohort studies with greater reliability [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations